2014
DOI: 10.1002/ange.201403839
|View full text |Cite
|
Sign up to set email alerts
|

Size‐Dependent Water Structures in Carbon Nanotubes

Abstract: Water surrounded by hydrophobic interfaces affects a variety of chemical reactions and biological activities. Carbon nanotubes (CNTs) can be used to investigate the behavior of water at hydrophobic interfaces. Here, we determined the fundamental unit of water by evaluating the ice‐like cluster formation of water in the limited hydrophobic nanospaces of CNTs, using X‐ray diffraction and molecular simulation analysis. The water in CNTs with a diameter of 1 nm had fewer hydrogen bonds than bulk water under ambien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
35
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(43 citation statements)
references
References 42 publications
8
35
0
Order By: Relevance
“…These results were experimentally verified by our group using NMR spectroscopy [ 26 ]. Structural and vibrational studies [ 39 , 40 ] have also shown that water confined inside a CNT of size 3.0 nm acquires ice-like clusters, showing cooperative motion with high diffusion. In this work, water clusters can diffuse smoothly and fast into these nanopores.…”
Section: Resultsmentioning
confidence: 99%
“…These results were experimentally verified by our group using NMR spectroscopy [ 26 ]. Structural and vibrational studies [ 39 , 40 ] have also shown that water confined inside a CNT of size 3.0 nm acquires ice-like clusters, showing cooperative motion with high diffusion. In this work, water clusters can diffuse smoothly and fast into these nanopores.…”
Section: Resultsmentioning
confidence: 99%
“…(119; 120) Thus under ambient conditions, water within 8 Å CNTs is gas-like, whereas with 11 and 12 Å diameter CNTs the water is ice-like and stack into layers of pentagons or hexagons. (121; 122) For larger diameters still, e.g., 20-30 Å, bound waters form multiple nano-clusters.…”
Section: Negative Curvaturementioning
confidence: 99%
“…(121; 122) For larger diameters still, e.g., 20-30 Å, bound waters form multiple nano-clusters. (120) It is not surprising therefore that there is a non-monotonic relationship between diameter and relative Helmholtz free energy of filling;(121) diameters of 8 and 12 Å represents energy minima. Overall entropy dominates slightly for tube diameters less than 10 Å or greater than 16 Å, and enthalpy dominates for tubes between 11 and 12 Å.…”
Section: Negative Curvaturementioning
confidence: 99%
“…In more confined spaces, however, both of these movement mechanisms are limited; water molecules show less mobility, and could also observe even ice-like behavior in the more restricted end of the interval. [52,53] With less available space to contain water molecules, the number of hopping points is fewer. This is the case for the movement of protons through hydrated graphene interlayer, whose hydrophobicity helps with confining water.…”
Section: Resultsmentioning
confidence: 99%